2021
DOI: 10.1021/acs.iecr.0c05725
|View full text |Cite
|
Sign up to set email alerts
|

Design of Hierarchically Structured Porous Boron/Nitrogen-Codoped Carbon Materials with Excellent Performance for CO2 Capture

Abstract: Environmental problems caused by excessive carbon dioxide emissions demand more than attention but realistic plans and specific actions as well. The development of materials with an efficient CO 2 adsorption performance is significant. In this paper, boric acid and ethylenediamine are used as boron and nitrogen sources, respectively, without using a hard/soft template, and a simple hydrothermal carbonization method is used to synthesize hierarchical porous carbon materials double-doped with boron and nitrogen.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…In terms of porosity, it is found that micropores also help in the CO 2 adsorption [46,47], as well as in the tiny mesopores and the specific area of the micropores [49]. Furthermore, it can be beneficial the reduction the SA and increase the CO 2 capacity even with the addition of heteroatoms [49]. In this case, the uniform distribution of the heteroatoms and the synergetic effect among different heteroatoms are beneficial for the gas's adsorption [49].…”
Section: Analysis Of Co 2 Adsorption In Correlation To the Porosity And The Elemental Functionalitiesmentioning
confidence: 98%
See 4 more Smart Citations
“…In terms of porosity, it is found that micropores also help in the CO 2 adsorption [46,47], as well as in the tiny mesopores and the specific area of the micropores [49]. Furthermore, it can be beneficial the reduction the SA and increase the CO 2 capacity even with the addition of heteroatoms [49]. In this case, the uniform distribution of the heteroatoms and the synergetic effect among different heteroatoms are beneficial for the gas's adsorption [49].…”
Section: Analysis Of Co 2 Adsorption In Correlation To the Porosity And The Elemental Functionalitiesmentioning
confidence: 98%
“…The incorporation of S [46] or N [47,48] shows a beneficial result. In terms of porosity, it is found that micropores also help in the CO 2 adsorption [46,47], as well as in the tiny mesopores and the specific area of the micropores [49]. Furthermore, it can be beneficial the reduction the SA and increase the CO 2 capacity even with the addition of heteroatoms [49].…”
Section: Analysis Of Co 2 Adsorption In Correlation To the Porosity And The Elemental Functionalitiesmentioning
confidence: 99%
See 3 more Smart Citations